(untitled) (Bangladesh Journal of Bioethics, 2012)
When the achievement of women leadership in Science and technology (S&T) is heighten in developed nations in comparison to women in developing countries, it is unfortunate that women are invariably left below, rarely reaching decision-making positions in S&T in Bangladesh. In Bangladesh, Prime Minister and Leader of Opposition are female but when it comes to leadership in science, it is difficult to find a Marie Curie in Bangladesh. Men are twenty times more likely than women to reach the top level positions in research. Women are underrepresented in almost in all scientific boards. The scarcity of women in senior positions in such bodies inevitably means that their opinions are less likely to be voiced in policy and decisionmaking processes, which may lead to bias decision-making and priority setting in scientific research. The causes of lower representation of women in S&T are discussed. All the causes raise ethical questions and violate the Universal Declaration of Human Rights (UDTH). Millennium development goals can never be accomplished without the active participation of women who represent 50 percent of the population, particularly their involvement in science education. Based on this analysis, a change of culture is required to improve gender imbalance in decision-making level in science. DOI: http://dx.doi.org/10.3329/bioethics.v2i1.9812 Bangladesh Journal of Bioethics 2011; 2(1): 13-17